MEDIA CRIMINOLOGY AS AN INSTRUMENT OF SOCIAL TAGING - Rodrigues de Oliveira Souto, Igor (2021)
This article aims to analyze social etiquette and media criminology, punctuating its consequences and limits, in an attempt to mitigate its possible damage. Labeling approach is the name given to the stigmatization of individuals in order to marginalize them and, eventually, imprison them. Chronologically, criminological theories have been developed. Sociologists developed theses, so that each new thesis confronted the previous one. The labeling approach emerged shortly after the positive theory and the theory of criminal subcultures. The main approach of the label's brand is to treat only a portion of the population in a discriminatory and exhaustive manner, that is: the most needy portion, in terms of purchasing power. As a kind of unfolding of labeling approach, media criminology emerged, which is nothing more than a form of manipulation exercised by the media that endorses the stigmatization of conformity. The media reinforces the idea of ​​stereotypes and constantly hints at the cruel treatment that, in the opinion, the adjusted defendants should receive. The research becomes relevant to address the value judgments that are made based on physical types, places of residence, societies, skin color, etc., all due to labeling approach and media criminology. The methodology used was literature review, through doctrinal analysis of some authors. In this sense, it should be noted that the theoretical framework is based on Alessandro Baratta (2002) and Zaffaroni (2012), two of the main exponents with regard to the themes under review. Thus, it is expected to contribute to the knowledge of the intricacies of labeling approach and media criminology and, consequently, to demystify the figure of the criminal, in order to promote a reflection on possible injustices committed in the face of some citizens as a result of judgments, precipitated and endowed with pure stigmatization